Inflation, Rice Prices, Production and Farmers Terms of Trade within AD–AS Framework - Nur Eka Sashi (Pattimura University, 2026)
Study analyzed influence of inflation, national rice prices, and rice production on the exchange rate of farmers in Indonesia through the Aggregate Demand-Aggregate Supply (AD-AS) model. Exchange rate of farmers is one of the indicators of farmers' welfare. Use research data is monthly data 2020 - 2024 total of 60 observations. Analysis was regressed with Newey-West autocorrelation consistent standard error to overcome autocorrelation and all disstationary variables through the Dickey-Fuller Augmentation test to increase validity through the Ordinary Least Square formula. Using statistical tests of Stata software data processors in the analysis of time series data on inflation variables, rice prices, rice production and farmers' exchange rates on a national scale. Results of study show that inflation has a negative and insignificant effect on the NTP, rice prices have a positive and significant influence. On the other hand, rice production has a negative and insignificant influence this period on NTP because there is a possibility of an imbalance between supply of rice prices and market demand. Findings support understanding of AD-AS approach where inflation, rice prices play a role as a factor in market demand, rice production as a market supply. Studies contribute empirically to the context of agricultural economics.